"Virtual Reality on Infinite Bandwidth": Vikram Chandra interviewed by Maria-Sabina Alexandru. - Alexandru, Maria-Sabina (Journal of Commonwealth Literature, 2005)
The article presents an interview with novelist Vikram Chandra. Chandra talks about her novel "Red Earth and Pouring Rain" and discusses how her experience as a computer programmer and as a knowledgeable Internet user influences her writing. When asked about the merging of virtual reality and fiction, Chandra relates it to the South Korean computer gaming culture.